Pengaruh Pendidikan Keluarga dan Literasi Ekonomi Terhadap Kompetensi Berwirausaha di Era 4.0 pada Siswa Kelas XI SMA 1 Rejotangan Tulungagung - Heningdra, Ajeng Rahayu; Rindrayani, Sulastri Rini (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Entrepreneurial competency is one of the main goals in the education process, in encouraging it it can then be formed through several factors, namely family education and economic literacy which work together to form an entrepreneurial mentality. Students who grow up in families that encourage creativity, responsibility and innovation will tend to have a proactive attitude towards business opportunities. The combination of supportive family education and strong economic literacy will be able to create a solid foundation for students to have entrepreneurial competence in the 4.0 era. This research method uses a quantitative approach with multiple linear regression analysis. The sample in this research was 100 students of XI SMAN 1 Rejotangan Tulungagung. Questionnaires were distributed by random sampling or at random. The research results show that: 1) There is an influence of family education on 4.0 era entrepreneurial competence in class XI students of SMA 1 Rejotangan Tulungagung. The family education factor is important because it can provide a direct impact and insight into students' learning directly, whether intentionally or not. 2) There is an influence of economic literacy on entrepreneurial competence in the 4.0 era in class XI students at SMA 1 Rejotangan Tulungagung. The economic literacy factor can become a student's self-development in building their entrepreneurial competence, based on the variety of knowledge they have. 3) There is an influence of family education and economic literacy on 4.0 era entrepreneurial competence in class XI students at SMA 1 Rejotangan Tulungagung. This second factor is an important part of family education and economic literacy which work together in forming an entrepreneurial mentality.